Controlling Risks in the Compounding Process of Individually Formulated Parenteral Nutrition: Use of the FMECA Method (Failure modes, effects, and Criticality Analysis) - Royer Mathilde; Libessart Maïté; Dubaele Jean-Marc; Tourneux Pierre; Marçon Fréderic (De Gruyter, 2020)
Parenteral nutrition (PN) in the neonatal intensive care unit (NICU) involves a succession of risky processes. The objective was to identify and prioritize the risks associated with PN in order to improve the quality of the pathway. A failure modes, effects, and criticality analysis (FMECA) was used to identify potential PN pathway failure modes. A multidisciplinary working group conducted a functional analysis of the processes, then listed the failure modes (FM). The FM criticality was assessed on a scale from 1 to 5 for occurrence (O), severity (S), and detection (D). The risk priority number (RPN), ranging from 1 to 125, was calculated. The FMECA identified 99 FM (prescription (n=28), preparation (n=48), and administration (n=23)). The median RPN was 12, with scores ranging from 3 to 48. 25 % of the scores had an RPN>21.75.